Comprehensive analysis of SPL gene family and miR156a/SPLs in the regulation of terpenoid indole alkaloid biosynthesis in Catharanthus roseus L - Yaojie Zhang; Xiaofan Ni; Xueqing Fu; Ayat Taheri; Wei Zhang; Pin Liu; Hang Liu; Ling Li; Yuliang Wang; Kexuan Tang (BMC Plant Biology)
Abstract Background Catharanthus roseus (C. roseus), belongs to the dogbane family Apocynaceae, is the source of various terpenoid indole alkaloids (TIAs) with excellent antitumor properties, including vinblastine, vincristine, ajmalicine, serpentine, vindoline, and catharanthine. However, TIAs are widely used in clinical anticancer research, their content is extremely low in plants, and currently insufficient to meet market demand. Therefore, exploring TIAs regulation is essential to improve TIAs yield. Numerous transcription factors have been shown to be involved in vinblastine biosynthesis, while the function of SPL members (CrSPL) has not yet been investigated in C. roseus. SPL genes regulate both plant growth and development as well as metabolite accumulation. Results In this study, genome-wide analysis identified fourteen CrSPL genes. The analysis included their gene structure, phylogenetic relationships, spatio-temporal expression profiles, response to methyl jasmonate and microRNA interactions. The yeast-one-hybrid (Y1H) and Dual-Luciferase (Dual-Luc) assays and transient overexpression show that CrSPLs can directly regulate the vinblastine biosynthesis pathway. The Cro-microRNA member, Cro-miR156a, can efficiently inhibit the activity of CrSPLs members and TIAs pathway genes. Conclusions Cro-miR156a and CrSPLs regulate TIAs biosynthesis, and this study provides a promising reference for investigating the roles of CrSPL TFs in regulating TIAs biosynthesis in C. roseus.